Application of Macrophage Subtype Analysis in Acute Lung Injury/Acute Respiratory Distress Syndrome - Jiajia Tang; Jun Shi; Zhihai Han; Xuxin Chen (Frontiers in Bioscience-Landmark)
Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is a common critical illness. Supportive therapy is still the main strategy for ALI/ARDS. Macrophages are the predominant immune cells in the lungs and play a pivotal role in maintaining homeostasis, regulating metabolism, and facilitating tissue repair. During ALI/ARDS, these versatile cells undergo polarization into distinct subtypes with significant variations in transcriptional profiles, developmental trajectory, phenotype, and functionality. This review discusses developments in the analysis of alveolar macrophage subtypes in the study of ALI/ARDS, and the potential value of targeting new macrophage subtypes in the diagnosis, prognostic evaluation, and treatment of ALI/ARDS.